2009
DOI: 10.3174/ajnr.a1640
|View full text |Cite
|
Sign up to set email alerts
|

Putaminal Volume in Frontotemporal Lobar Degeneration and Alzheimer Disease: Differential Volumes in Dementia Subtypes and Controls

Abstract: BACKGROUND AND PURPOSE:Frontostriatal (including the putamen) circuitϪmediated cognitive dysfunction has been implicated in frontotemporal lobar degeneration (FTLD), but not in Alzheimer disease (AD) or healthy aging. We sought to assess putaminal volume as a measure of the structural basis of relative frontostriatal dysfunction in these groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
48
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 27 publications
13
48
0
Order By: Relevance
“…Regions of interest studies have demonstrated striatal atrophy including the caudate and the putamen in bvFTD [59,60]. The present results are in line with PET studies with hypometabolism in the striatal region [53,61] and in accordance with previous neuropathology results as well [62].…”
Section: Discussionsupporting
confidence: 82%
“…Regions of interest studies have demonstrated striatal atrophy including the caudate and the putamen in bvFTD [59,60]. The present results are in line with PET studies with hypometabolism in the striatal region [53,61] and in accordance with previous neuropathology results as well [62].…”
Section: Discussionsupporting
confidence: 82%
“…Our recent volumetric studies of FTLD showed reductions in the volume of the caudate by up to 25% of control volume (FTD subtype) and by up to 13% of control volume in the putamen (PNFA subtype), in contrast to minimal volumetric change in AD compared to controls (Looi et al, 2008b(Looi et al, , 2009b. We also demonstrated that there was a gradation in severity of atrophy consistent with the severity of theoretical frontostriatal dysfunction, with greatest atrophy in the FTD subtype of FTLD for the caudate and more uniform atrophy across all FTLD subtypes in the putamen.…”
Section: Introductionmentioning
confidence: 97%
“…Due to modulation of the tissue images, the effect of normalization (ie, extension or shrinkage of the investigated structure) was compensated for so that the computed volume represented the volume of the original structure in native space (Fig 1). 9 The manual delineation of the caudate was performed separately in both hemispheres in reference to the established protocol by Looi et al 10,11 The volumes in each section (in-section volume) were calculated by multiplying the voxel number of each trace by the voxel volume and dividing this value by the magnification factor. The total volumes were calculated as the sum of all in-section volumes.…”
Section: Mr Imaging Data Processing and Automated Abvmentioning
confidence: 99%